UK military women: mental health, military service and occupational adjustment. (12th February 2020) - Jones, N; Jones, M; Greenberg, N; Phillips, A; Simms, A; Wessely, S
Abstract: Background: Recently, the UK Armed Forces have revised the ground close combat role to include women. Aims: To assess the potential mental health impact of this initiative we examined gender differences in deployment patterns, work strain, occupational factors, mental health, alcohol use and help-seeking following operational deployment. Methods: The study was a secondary analysis of self-report survey data; 8799 men (88%) and 1185 women (12%) provided data. A sub-sample (47%, n = 4659) provided data concerning post-deployment help-seeking. The latter consisted of 408 women (8.8%) and 4251 men (91%). Results: With the exception of alcohol misuse, which was significantly lower for women, women reported significantly more common mental disorder symptoms, subjective depression and self-harm. Women were significantly more likely to seek help from healthcare providers. Men were significantly more likely to have deployed operationally and for longer cumulative periods. Subjective work strain, but not job control, was significantly lower for women whose military careers were significantly shorter. Post-traumatic stress disorder (PTSD) symptom intensity was similar to men. Conclusions: With the exception of PTSD and alcohol misuse, UK military women experience more mental health-related problems than military men. This finding was not related to the more arduous aspects of military service as women served for shorter times, deployed less and for shorter cumulative periods and were less likely to report work-related stress.